BIM e Realidades Estendidas: as tecnologias XR auxiliando na concepção do Projeto Arquitetônico - Aguiar, Beatriz Natália Guedes Alcoforado (2024)
The teaching of architecture, historically based on abstract approaches, requires students to create and visualize concepts for which they have not yet fully developed their skills. To address this issue, it is essential for 21st-century researchers to integrate emerging technological advances into the educational process. Addressing the research question, “How can extended reality (XR) technologies, associated with building information modeling (BIM), support the teaching and learning of the architectural design process in the stages of conception and development?”, this study hypothesizes that XR technologies can directly influence architecture students' understanding during the design creation process, thereby contributing to the continuous improvement of their representational skills. The research aims to systematize the use of XR technologies, in conjunction with BIM, for teaching and learning architectural design in the conception and development stages. Employing the action research method, the study is structured into three phases: exploration, description, and prescription. Each phase was applied cyclically over three semesters in the Architecture and Urbanism program at the Federal University of Ceará. The study culminated in the development of an Implementation Model, accompanied by an Implementation Guide and validated Didactic Experiences. These outputs provide both practical and theoretical support for integrating XR and BIM into architectural design education, promoting an innovative pedagogical approach that enhances students' spatial understanding, reduces design errors, and strengthens immersive learning within the academic context.